Liquefaction Potential based on Earthquake History in Sanana Region, Sula Island Regency, North Maluku, Indonesia - Pajrin, Ulfia Sari; Zakaria, Zufialdi; Sophian, Raden Irvan; Khoirullah, Nur; Mubarak, Aziez; Basuki, Jodi Prakoso (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
Sula Islands is a region in Maluku Province that is very vulnerable to earthquakes because it is located on an active seismic line. One of the disasters that often accompanies earthquakes is liquefaction. Sandy soil in a saturated condition will lose its strength when an earthquake occurs, thus endangering the building above it. The aim of the study was to determine seismicity and estimate the liquefaction potential of the earthquake history and CPT test in the Sanana region and its surroundings. The method in this study uses a